81 Group interventions for children with tourette syndrome: a 12 month follow up study of a randomised controlled trial comparing comprehensive behavioural intervention and psycho-education. (4th October 2017) - Dabrowski, Julia; King, John; Edwards, Katie; Yates, Rachel; Heyman, Isobel; Zimmerman-Brenner, Sharon; Murphy, Tara
Abstract : Background: Comprehensive Behavioural Intervention for Tics (CBIT) is a behavioural therapy with strong empirical support for its effects on tic severity when offered as an individual therapy 1 and emerging evidence for its effectiveness in a group format. 2 This study compared the long-term effects of CBIT and psycho-educational groups on tic severity, neuropsychological functioning, quality of life (QOL) and school attendance. Method: This is a follow-up study to a single-blinded, randomised controlled trial. Twenty-eight children that completed either psycho-educational or CBIT group treatment took part in this 12 month follow-up. Participants had a mean age of 12.1 years and a diagnosis of either Tourette Syndrome (TS) or Chronic Tic Disorder. Outcomes included the YGTSS, direct video observation, neuropsychological functioning measures (response inhibition, cognitive flexibility and motor dexterity), the GTS-QOL and school attendance data. Results: Both groups demonstrated long-term improvements in tic severity (p<0.001, ηp 2 = 0.32), with continued improvement across the follow-up period ( F (1, 26) = 7.52, p=0.011, ηp 2 =0.22). Self-reported QOL also improved during the follow-up period ( F (1, 19) = 5.73, p=0.027, ηp 2 = 0.23). The CBIT group demonstrated greater improvement in tic suppression ability (p=0.019, ηp 2 = 0.146) and a correlation was found between QOL and tic suppression ability at follow-up ( r =−0.517, p=0.008). Both groups improved in school attendance (p=0.004, ηp 2 = 0.304). Conclusion: Groups were associated with long-term improvements in tic severity, QOL and school attendance, offering support for the long-term acceptability of these group treatments for TS. The CBIT group showed a greater improvement in tic suppression ability over time and increased tic suppression ability was associated with improved quality of life, suggesting a relationship between self-reported QOL and a child's sense of control over their tics through the use of behavioural strategies. References: . J McGuire, J Piacentini, EA Brennan, AB Lewin, TK Murphy, BJ Small, EA Storch. A meta-analysis of behavior therapy for Tourette syndrome. Journal of psychiatric research 2014;50:106–112. . R Yates, K Edwards, J King, O Luzon, M Evangeli, D Stark, F McFarlane, I Heyman, B Ince, J Kodric, T Murphy. Habit Reversal Training and Educational group treatments for children with Tourette syndrome: A preliminary randomised controlled trial. Behaviour Research and Therapy 2016.